2018
DOI: 10.1093/mnras/sty3009
|View full text |Cite
|
Sign up to set email alerts
|

Lyman α photons through rotating outflows

Abstract: Outflows and rotation are two ubiquitous kinematic features in the gas kinematics of galaxies. Here we introduce a semi-analytic model to quantify how rotating outflows impact the morphology of the Lyman-α emission line. The model is contrasted against Monte Carlo radiative transfer simulations of outflowing gas with additional solid body rotation. We explore a range of neutral Hydrogen optical depth of 10 5 ≤ τ H ≤ 10 7 , rotational velocity 0 ≤ v rot /km s −1 ≤ 100 and outflow velocity 0 ≤ v out /km s −1 ≤ 5… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…The asymmetric feature of Lyα emission from high-z galaxies is theoretically expected due to absorption by the interstellar medium (ISM) and IGM. Interaction with an outflowing ISM provides easier escape routes for the red wing of Lyα (e.g., Ahn et al 2001;Dijkstra 2014), thus the redshifted asymmetric Lyα emission line profile is often explained by common galactic outflows (e.g., Verhamme et al 2006;Gronke et al 2015;Remolina-Gutiérrez & Forero-Romero 2019), which could be boosted by cosmic ray (Gronke et al 2018) and Lyα feedback (Smith et al 2017;Kimm et al 2018). Importantly, recent studies on Lyα profiles with Green Peas, a local analogue of a high-z LAEs, have revealed more complex processes related to their Lyα profiles (e.g., Yang et al 2016Yang et al , 2017aVerhamme et al 2018;Orlitová et al 2018).…”
Section: Lyα Emission Propertiesmentioning
confidence: 99%
“…The asymmetric feature of Lyα emission from high-z galaxies is theoretically expected due to absorption by the interstellar medium (ISM) and IGM. Interaction with an outflowing ISM provides easier escape routes for the red wing of Lyα (e.g., Ahn et al 2001;Dijkstra 2014), thus the redshifted asymmetric Lyα emission line profile is often explained by common galactic outflows (e.g., Verhamme et al 2006;Gronke et al 2015;Remolina-Gutiérrez & Forero-Romero 2019), which could be boosted by cosmic ray (Gronke et al 2018) and Lyα feedback (Smith et al 2017;Kimm et al 2018). Importantly, recent studies on Lyα profiles with Green Peas, a local analogue of a high-z LAEs, have revealed more complex processes related to their Lyα profiles (e.g., Yang et al 2016Yang et al , 2017aVerhamme et al 2018;Orlitová et al 2018).…”
Section: Lyα Emission Propertiesmentioning
confidence: 99%
“…Indeed, analytical studies have been beneficial in elucidating fundamental escape properties and mechanisms (Harrington 1973;Neufeld 1990;Loeb & Rybicki 1999;Hansen & Oh 2006;Lao & Smith 2020), but are also complemented by tests in slab and spherical geometries (Ahn et al 2002;Zheng & Miralda-Escudé 2002;Dijkstra et al 2006;Verhamme et al 2006;Smith et al 2017a). Beyond this there are nontrivial qualitative and quantitative insights revealed by simulations of expanding shell environments (Verhamme et al 2008;Gronke et al 2015;Yang et al 2017;Orlitová et al 2018;Gurung-Lopez et al 2021), clumpy multiphase media (Dijkstra & Kramer 2012;Laursen et al 2013;Duval et al 2014;Li et al 2021b), and other idealized setups Zheng & Wallace 2014;Smith et al 2015;Gronke et al 2017;Remolina-Gutiérrez & Forero-Romero 2019;Seon & Kim 2020;Song et al 2020). However, although the intuition and physics is generally applicable, the path towards reliable Ly𝛼 predictions based on hydrodynamical simulations is inherently tied to the success of galaxy modelling (Dayal & Ferrara 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The kinematics of the gas also needs to be taken into account. All these processes give rise to different line profile shapes depending on the conditions surrounding the emitter galaxy (Shapley et al 2003;Karman et al 2014;Martin et al 2015;Dijkstra 2017;Hernán-Caballero et al 2017;Karman et al 2017;Bridge et al 2018;Erb et al 2018;Gurung-Lopez et al 2018;Nakajima et al 2018;Orlitová et al 2018;Sobral et al 2018;Vanzella et al 2018;Kimm et al 2019;Marchi et al 2019;Remolina-Gutiérrez & Forero-Romero 2019;Smith et al 2019).…”
Section: Introductionmentioning
confidence: 99%